2014
DOI: 10.1039/c4an01469c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a field sampling method based on magnetic nanoparticles for the enrichment of pesticides in aqueous samples

Abstract: A field sampling method based on magnetic core-shell silica nanoparticles was developed for field sampling and the enrichment of low concentrations of pesticides in aqueous samples. The magnetic nanoparticles could be easily extracted from water samples by a custom-made magnetic nanoparticle collector. The recovery of 15 mg of magnetic particles from a 500 mL water sample was 90.8%. Mixtures of seven pesticides spiked into pure water and pond water were used as marker samples to evaluate the field sampling met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The recoveries of OCPs for three spiked aqueous samples ranged from 73.6 to 107.0%. A field sampling method based on magnetic core-shell silica nanoparticles Water Environment Research, Volume 87, Number 10-Copyright © 2015 Water Environment Federation was developed for field sampling and enrichment of low concentrations of pesticides in aqueous samples(Zhang, Sheng, et al, 2014). Mixtures of seven pesticides spiked into pure water and pond water were used as marker samples to evaluate the field sampling method.…”
mentioning
confidence: 99%
“…The recoveries of OCPs for three spiked aqueous samples ranged from 73.6 to 107.0%. A field sampling method based on magnetic core-shell silica nanoparticles Water Environment Research, Volume 87, Number 10-Copyright © 2015 Water Environment Federation was developed for field sampling and enrichment of low concentrations of pesticides in aqueous samples(Zhang, Sheng, et al, 2014). Mixtures of seven pesticides spiked into pure water and pond water were used as marker samples to evaluate the field sampling method.…”
mentioning
confidence: 99%
“…24 Analytical parameters of the proposed method were investigated and good linear 25 range (4.0 -400.0 ng·mL −1 ), limits of detection (LOD, 0.67 ng·mL -1 ), limits of 26 quantification (LOQ, 2.2 ng·mL -1 ) and precision (RSD of 6.7%, n = 5) were obtained. 27 This proposed method was successfully applied to the analysis of the real samples 28 with good spiked recoveries over the range of 91.4-99.6%, proving that this method 29 was competitive in practical applications. The results indicated that the developed 30 method would be a green method for rapid determination of TDF at trace levels in real 31 samples.…”
mentioning
confidence: 90%
“…25 Various magnetic materials can be used as adsorbents. [26][27][28][29] Considering the structural feature of TDF, magnetically modied carbon nanotubes (CNTs) are considered to be extremely superior adsorbents due to their high specic surface area and large micropore volume, which have been utilized for the adsorption of a number of organic pollutants. [30][31][32][33][34] For the synthesis of magnetic hybrid materials, Fe has attracted considerable attention owing to its low coercivity, high saturation magnetization, chemical stability and electrical resistivity, which can make it an excellent material for magnetic resonance imaging (MRI) enhancement, magnetic recording media and magnetic separation.…”
Section: Chemically Tdf Is 9[(r)-2-[[bis[[(isopropoxycarbonyl)oxy]met...mentioning
confidence: 99%
See 1 more Smart Citation